2001
DOI: 10.1016/s0893-133x(00)00181-0
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous 5-HT Tonically Inhibits Spontaneous Firing Activity of Dorsal Hippocampus CA1 Pyramidal Neurons Through Stimulation of 5-HT1A Receptors in Quiet Awake Rats In Vivo Electrophysiological Evidence

Abstract: The present study was performed to examine an overall effect of endogenous serotonin (5-HT) on the spontaneous firing activity of the dorsal hippocampus CA1 pyramidal neurons in quiet awake rats. A selective 5-HT 1A antagonist N-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-N-(2-pyridinyl)cyclohexanecarboxamide (WAY-100635: 0.03-0.2 mg/kg, s.c.) It has been shown that there are at least 14 serotonin (5-HT; 5-hydroxytryptamine) receptor subtypes over seven distinct receptor subfamilies. Among these seven recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…In mammals, serotonergic activity has been demonstrated to limit hippocampal output via 5-HT1A receptors on pyramidal neurons; while 5-HT4 receptor stimulation and 5-HT induced inhibition of GABAergic interneurons enhances hippocampal output (Andrade and Nicoll, 1987;Andrade and Chaput, 1991;Gulyás et al, 1999;Kasamo et al, 2001;Chapin et al, 2002). In our data, there was a trend towards higher plasma cortisol concentrations in fish that were not reintroduced to their subordinate partners after social defeat (c.f.…”
Section: Discussionsupporting
confidence: 46%
“…In mammals, serotonergic activity has been demonstrated to limit hippocampal output via 5-HT1A receptors on pyramidal neurons; while 5-HT4 receptor stimulation and 5-HT induced inhibition of GABAergic interneurons enhances hippocampal output (Andrade and Nicoll, 1987;Andrade and Chaput, 1991;Gulyás et al, 1999;Kasamo et al, 2001;Chapin et al, 2002). In our data, there was a trend towards higher plasma cortisol concentrations in fish that were not reintroduced to their subordinate partners after social defeat (c.f.…”
Section: Discussionsupporting
confidence: 46%
“…In the present study, systemic injection of WAY 100,635 increased the firing activity of one-third of hippocampal cells in control rats. Although this disinhibition has not been reported in previous studies (Haddjeri et al, 1998a, b;Rueter et al, 1998;Besson et al, 2000), Kasamo et al (2001) have shown that WAY 100,635 administration significantly increased the firing activity of CA 1 pyramidal neurons of the dorsal hippocampus in quiet awake rats. This indicates that in nontreated rats endogenous 5-HT would tonically inhibit the spontaneous firing activity of CA 1 pyramidal neurons through the activation of 5-HT 1A receptors.…”
Section: Discussionmentioning
confidence: 58%
“…Recent behavioral studies have indicated that dorsohippocampal 5-HT 1A receptors are involved in contextual fear conditioning in mice (Stiedl et al, 2000). We showed that endogenous 5-HT tonically inhibits the spontaneous firing activity of dorsal hippocampus CA 1 pyramidal neurons via postsynaptic 5-HT 1A receptors in quiet awake rats (Kasamo et al, 2001). Despite conflicting results, most studies have demonstrated increased 5-HT release in the hippocampus during various stress conditions (Vahabzadeh and Fillenz, 1994;Matsuo et al, 1996;Wilkinson et al, 1996;Rueter et al, 1996).…”
Section: Introductionmentioning
confidence: 88%
“…We reported that the spontaneous firing activity of dorsal hippocampus CA 1 pyramidal neurons is tonically inhibited by endogenous 5-HT via postsynaptic 5-HT 1A receptors (Kasamo et al, 2001). The present study investigates whether this inhibition is produced through postsynaptic 5-HT 1A receptors.…”
Section: Blockade Of 5-ht 1a Receptors By Way-100635 and Way-100135mentioning
confidence: 99%